Narcissism but Not Criminality Is Associated With Aggression in Women: A Study Among Female Prisoners and Women Without a Criminal Record - Kalemi, Georgia; Michopoulos, Ioannis; Efstathiou, Vasiliki; Konstantopoulou, Foteini; Tsaklakidou, Domna; Gournellis, Rossetos; Douzenis, Athanassios (Frontiers in Psychiatry, 2019)
Female criminality and aggression has drawn research attention during the past decades. Only a few studies have attempted to examine those variables among females, while none of them included a comparison between delinquent and non delinquent individuals. The present study examines the effect of self-esteem, self-perception, narcissism and socio-demographic factors on aggression among female inmates and women without criminal record. One hundred fifty-seven female inmates in the Attica’s Korydallos Female Prison and 150 women with no criminal record were assessed with Buss & Perry Aggression Questionnaire, Rosenberg’s Self-esteem Scale, Narcissistic Personality Inventory-40 and the Self-Perception Profile for Adults. When inmates were compared to controls, it emerged that aggression could be independently predicted by higher levels of narcissistic personality traits and sociability, as well as lower age, lower education, lower self esteem and lower levels of self-perception items including nurturance, job competence and athletic abilities. Aggression was not predicted by the group (inmates vs. controls). Within female inmates, independently of the type of their offence (convicted for violent vs. non-violent crimes), it was found that lower job competence, higher narcissistic personality traits and a history of childhood maltreatment could predict higher aggression. Our results support the notion that female aggression differs from male and highlight the significant parameters that may predict aggression either among women (inmates and non-deliquent women) or among female inmates (violent or non-violent crimes) It is the presence of narcissistic traits which predict aggression rather than criminality in general, including violent and non-violent crimes.